Comparison of apical microleakage of mineral trioxide aggregate, calcium-enriched mixture cement and biodentine as root end filling materials - Abbas Ghobadi; Ali Soleymani; Hemmat Gholinia (Babol University of Medical Sciences, 2020)
Introduction: The aim of this in vitro study was to assess the apical microleakage of mineral trioxide aggregate (MTA), calcium enriched mixture (CEM) cement, and biodentine. Materials & Methods: The study was performed on 76 single-canal human teeth. Root canals were prepared by ProTaper rotary system, obturated with gutta-percha. Thereafter, the apical section of the teeth was cut from 3 mm above the apex, and 3 mm of gutta-percha was removed by an ultrasonic device from the apical part of the root canals. Then, 60 teeth were randomly assigned to 3 groups and filled with MTA, CEM cement, and biodentine. Control groups were also prepared. All surfaces of the samples were covered with two layers of nail polish, except for the surfaces near the apical filling. In each group, half of the samples were immersed in indian ink for 3 days and the other half for 7 days. After clearing, the samples were examined using stereo microscope with 20x magnification and dye penetration was evaluated. Data analysis was performed using Repeated measures and One-way ANOVA and p<0.05 was considered significant. Results: The mean microleakage for MTA, CEM cement and biodentine on the third day were 2576.80 and 2567.60, 2370.20 and the mean on the seventh day were 2431.50, 1516.50 and 1560.70, respectively. The mean leakage was not statistically different in samples on the third and seventh days. The difference of microleakage was statistically significant among these materials. Conclusion: It seems the biodentine compared to MTA and CEM cement have better apical sealing ability.